2010
DOI: 10.5032/jae.2010.03088
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Future Secondary Agricultural Education Teachers To Work With Students With Learning Disabilities: Reports from Teacher Educators

Abstract: Secondary agricultural education programs are enrolling increasing numbers of students with various disabilities. One consequence is that pre-service teachers are expressing a need for additional preparation to work with such students. This study was conducted to examine the preparation that preservice teachers receive to work with students with learning disabilities in secondary agricultural education programs. The target population for the study was agricultural teacher educators who plan and in some situati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…This investigation also found the women believed most of their professional development experiences in special education were inadequate because they were fast-paced, repetitive, and not specific to SBAE. This conclusion was consistent with prior research, which has indicated preservice courses focused on students with special needs have often not been extensive enough to help SBAE teachers feel prepared to teach students with special needs in their programs (Aschenbrener et al, 2010;Faulkner & Baggett, 2010;Kessell, 2009;Ruhland & Bremer, 2002;Ramage et al, 2021;Roberts et al, 2020;Stair et al, 2019). It was further concluded that even if participants received preservice education on teaching students with special needs, the limited extent of the courses failed to provide adequate time for interpretation and to develop positive perceptions when accommodating students with special needs.…”
Section: Conclusion Discussion Implications and Recommendationssupporting
confidence: 90%
See 1 more Smart Citation
“…This investigation also found the women believed most of their professional development experiences in special education were inadequate because they were fast-paced, repetitive, and not specific to SBAE. This conclusion was consistent with prior research, which has indicated preservice courses focused on students with special needs have often not been extensive enough to help SBAE teachers feel prepared to teach students with special needs in their programs (Aschenbrener et al, 2010;Faulkner & Baggett, 2010;Kessell, 2009;Ruhland & Bremer, 2002;Ramage et al, 2021;Roberts et al, 2020;Stair et al, 2019). It was further concluded that even if participants received preservice education on teaching students with special needs, the limited extent of the courses failed to provide adequate time for interpretation and to develop positive perceptions when accommodating students with special needs.…”
Section: Conclusion Discussion Implications and Recommendationssupporting
confidence: 90%
“…Because a gap may exist in content knowledge about specific disability categories and strategies when teaching students with special needs, is it possible that further marginalization of students with special needs may be occurring in classrooms? For example, if women SBAE teachers perceive students to be of low ability or are unaware of how to effectively teach certain students, they may unintentionally reduce experiences and opportunities for those learners (Aschenbrener et al, 2010;Faulkner & Baggett, 2010;Jobling & Moni, 2004;Johnson et al, 2012;Kessell, 2009;Ruhland & Bremer, 2002;Stair et al, 2019).…”
Section: Conclusion Discussion Implications and Recommendationsmentioning
confidence: 99%